Protocol for CONSORT-SPI: an extension for social and psychological interventions. - Montgomery, P; Grant, S; Hopewell, S; Macdonald, G; Moher, D; Michie, S; Mayo-Wilson, E (2013)
BACKGROUND: Determining the effectiveness of social and psychological interventions is important for improving individual and population health. Such interventions are complex and, where possible, are best evaluated by randomised controlled trials (RCTs). The use of research findings in policy and practice decision making is hindered by poor reporting of RCTs. Poor reporting limits the ability to replicate interventions, synthesise evidence in systematic reviews, and utilise findings for evidence-based policy and practice. The lack of guidance for reporting the specific methodological features of complex intervention RCTs contributes to poor reporting. We aim to develop an extension of the Consolidated Standards of Reporting Trials Statement for Social and Psychological Interventions (CONSORT-SPI). METHODS/DESIGN: This research project will be conducted in five phases. The first phase was the project launch, which consisted of the establishment of a Project Executive and International Advisory Group, and recruitment of journal editors and the CONSORT Group. The second phase involves a Delphi process that will generate a list of possible items to include in the CONSORT Extension. Next, there will be a formal consensus meeting to select the reporting items to add to, or modify for, the CONSORT-SPI Extension. Fourth, guideline documents will be written, including an explanation and elaboration (EandE) document that will provide detailed advice for each item and examples of good reporting. The final phase will comprise guideline dissemination, with simultaneous publication and endorsement of the guideline in multiple journals, endorsement by funding agencies, presentations at conferences and other meetings, and a dedicated website that will facilitate feedback about the guideline. CONCLUSION: As demonstrated by previous CONSORT guidelines, the development of an evidence-based reporting guideline for social and psychological intervention RCTs should improve the accuracy, comprehensiveness, and transparency of study reports. This, in turn, promises to improve the critical appraisal of research and its use in policy and practice decision making. We invite readers to participate in the project by visiting our website (http://tinyurl.com/CONSORT-study).